Development of novel patient selection criteria for a short stay endovascular aneurysm repair pathway: Improving patient selection for short stay endovascular aneurysm repair. (February 2020) - Preece, Ryan; Shaw, Sarah; Wiltshire, Joseph; Stenson, Katherine; Budge, James; De Bruin, Jorg; Loftus, Ian; Holt, Peter; Patterson, Benjamin
Objectives: A short-stay endovascular aneurysm repair (SS-EVAR) pathway for infrarenal abdominal aortic aneurysms offers the potential to improve service efficiency and patient satisfaction by reducing the hospital length of stay. This study aimed to determine whether the implementation of a novel set of patient selection criteria for a theoretical SS-EVAR pathway could facilitate an expansion of the proportion of suitable patients, whilst maintaining patient safety and limiting unplanned emergency readmissions. Methods: Two SS-EVAR selection criteria (low and high risk) were generated based upon patient pre-operative comorbidities. The low risk criteria essentially selected fit and healthy individuals, whereas the high risk criteria included patients with a range of comorbidities that could still theoretically enable enrolment onto a SS-EVAR pathway. A retrospective analysis, whereby both criteria were applied to all elective EVARs recorded in the National Vascular Registry between 2013 and 2016 at a single tertiary vascular unit was performed. Rates and timings of postoperative complications, reinterventions and unplanned readmissions for patients meeting each criteria were assessed. Results: In total, 188 patients were included (92% male, mean age 75.4 ± 7.2 years). Twenty-nine patients (15%) met the low risk criteria. Two (7%) of these experienced an inpatient complication which were both detected within 24 h of operation (including one who required reintervention), and no patients in this group had an unplanned readmission within 30 days. One-hundred and ten patients (59%) met our high risk criteria and 19 (17%) experienced an inpatient complication, with 4 (4%) of these occurring beyond 24 h post-EVAR (three urinary problems and one acute on chronic kidney injury). Six (6%) of these patients required a reintervention; however, all of these complications were detected within 24 h. Two (2%) high risk cohort patients required unplanned readmission within 30 days for a femoral pseudoaneurysm and musculoskeletal back pain. Conclusions: With high risk patient selection criteria and appropriate post-operative safeguards, up to 60% of infrarenal abdominal aortic aneurysms patients could be safely enrolled onto a next-day discharge SS-EVAR pathway with minimal readmissions, thus allowing more effective resource utilisation.